Prevalence of body dysmorphic disorder in patients who are candidates and/or are submitted to aesthetic procedures in the specialty of plastic surgery: a systematic review with meta-analysis - Rafael Vilela Eiras Ribeiro; Gisele Botega Silva; Frederico Vieira Augusto (Revista Brasileira de Cirurgia Plástica, 2017)
This study aimed at showing the prevalence of body dysmorphic disorder (BDD) in patients who are candidates and/or are submitted to aesthetic procedures in the specialty of plastic surgery via a systematic review of the literature and a meta-analysis. To comply with the proposed objective, we analyzed the most relevant studies originally published in any language that were available in the National Library of Medicine (MEDLINE), Cochrane, and SciELO databases. Searches were performed using keywords associated with the theme and inclusion and exclusion criteria. Thus, the final sample of this study was composed of 15 publications, which were submitted to a meta-analysis. It can be confirmed that 12.5% of the patients who were candidates/submitted to aesthetic procedures in the specialty of plastic surgery had BDD. Of these, the majority were women (75.7%) with a mean age of 30 (± 10.5) years. Given the high number of patients with BDD attended to in the specialty, it is important that plastic surgeons focus on providing patients with adequate care to identify individuals who potentially have BDD and consequently conduct an interdisciplinary follow-up with the participation of psychologists and psychiatrists.